SOFA 2001 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Situation mondiale de l’alimentation et de l’agriculture Rome, 2001 322 pages + cédérom ISBN 92 5 104600 X Prix : 49 US$ / 53, 75 FAO Viale delle Terme di Caracalla, 00100 Rome, Italy Fax: + 39 06 57 05 33 60 E-mail: publications-sales@fao.o